Statistical Process Control (SPC) and Fuzzy-Failure Mode and Effect Analysis (F-FMEA) Approaches to Reduce Reject Products in Wine Bottle Rack Production Process at PT Alis Jaya Ciptatama - Nikma Wahyu Nurdaningsih; Elly Wuryaningtyas Yunitasari; Syamsul Ma'arif (OPSI, 2022)
PT Alis Jaya Ciptatama (AJC) is a company engaged in the furniture industry, where the products are exported. One of the products from PT AJC is a wine bottle rack. In the production of wine bottle racks at PT AJC, many product defects were found. Therefore, it is necessary to conduct further research to determine the quality of the product, so that the correct product quality improvement is obtained. The purpose of this study was to determine the limits of statistical control and the factors causing defects in wine bottle racks so that the quality improvement provided was right on target. The methods used in this research are Statistical Process Control (SPC) and Fuzzy Failure Mode and Effect Analysis (F-FMEA). SPC method is used to determine statistical control limits and factors causing product defects. The F-FMEA method is used to determine the priority of improvement in improving the quality of wine bottle racks. The results of the research related to the statistical control limits of the SPC method were obtained that the defective data were outside the statistical control limits. While the results of research related to the causes of product failure using the SPC method are human, machine, material, environmental, method, and measurement factors. Factors causing product failure were analyzed using the F-FMEA method so that improvement priorities were obtained, namely the lack of experience of workers with an FRPN value of 269.33. Improvements that need to be made by PT AJC include providing training to mill 1 workers and splitting the logs.